Reubicación urbana y vivienda de interés social en Cura Mori, Piura - Mejía Puccio, Daniela Andrea (2023)
The Cura Mori district, within the Piura department, was one of the most affected by El Fenómeno del Niño Costero in 2017. This is due to the fact that this district's population centers are situated close to the Piura River's flow. El Fenómeno del Niño Costero caused flooding and damage to the residents' homes, so they were relocated to shelters within the Cura Mori district, between kilometers 980 and 975 of the Panamericana Norte highway. Approximately 1,879 families settled in tents with the hope of later being relocated to proper housing; however, the government program Reconstrucción con Cambios was slow to assist the affected individuals, and as a result, they ended up building precarious homes where they still live to this day (2023). This is how Cura Mori's new residential zones were created from the land set aside for shelters. The purpose of this thesis is to design an urban complex and affordable housing proposal that addresses the socio-cultural, atmospheric, economic, and landscape needs to improve living conditions and reform the lives of the victims of the 2017 Fenómeno del Niño Costero who currently reside in Nuevo Chato Chico - Ciudad de Dios populated area, within the Cura Mori district. It also aims to improve their economic condition by generating additional income through the incorporation of agricultural activities as an urban component. To accomplish the stated goal, the study was first carried out, and numerous factors affecting the project's location in Nuevo Chato Chico and Ciudad de Dios were examined. These variables include the current situation of the place and the measures taken before and after the 2017 Fenómeno del Niño Costero, the historical aspect of the place, an analysis of the context, theories, and references that drive appropriate design for the newly populated area, and the legal aspect. A field visit was then conducted in which the authors interviewed critical stakeholders in the project and engaged in conversations with leaders of the populated areas at Kilometer 975 to build trust and encourage their involvement in the design process of the current thesis. Finally, the design and management plan for the Urban Relocation and Affordable Housing for the newly populated areas of Cura Mori, Piura (Plan RUVIS 975), was developed.